Trends und die Notwendigkeit der Wiederholung — Ein metareflexiver Blick auf die Forschungsgeschichte der Intertextualität der Johannesoffenbarung - SOMMER, Michael (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
This article addresses the fundamental categories of intertextuality research on the Revelation of John at a meta-level. It considers both historical-critical models of the author and the recipients of the Revelation, which are based on an intertextual readings, as well as on reader-oriented approaches to the last book of the bible. In addition to outlining the limitations of existing methodologies, the article aims to identify gaps in the research and stimulate further investigation.